Template-free synthesis of hierarchical hollow V2O5 microspheres with highly stable lithium storage capacity. Issue 5 (12th January 2017) - Li, Hangkong; Wang, Jiexi; Liu, Xiang; Sun, Qian; Djurišić, Aleksandra B.; Xie, Maohai; Mei, Ying; Tang, Chuyang Y.; Shih, Kaimin
Abstract : Hierarchical hollow V2 O5 microspheres synthesized by a facile solvothermal method and subsequent calcination exhibit excellent cycling performance. Abstract : Hollow V2 O5 microspheres were successfully synthesized by a solvothermal method and subsequent calcination. The rigid hollow V2 O5 cathode prepared in isopropanol solvent exhibited excellent cycling performance and rate capability. Within a voltage window of 2.5 to 4 V, a maximum specific discharge capacity of 128 mA h g −1 was delivered at 1 A g −1 . Even after 500 cycles, the capacity retention was 92.2%.